Gambaran Sedimen Urin Kristal Kalsium Oksalat Pada Pekerja Konveksi Di Desa Kalipucang Kecamatan Batang - Rizqi Nafisah; Fitrianingsih Fitrianingsih (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Urinary Tract Stones(BSK) is a condition in which oxalate stones (kidney stones) accumulate in the ureters, bladder or kidneys. Stone blockages that form in the urinary tract area are usually calcium oxalate stones. The formation of calcium oxalate crystals can be affected by the length of time a person sits while working. Convection workers require sitting for a long time while working. As a result, calcium ions that affect the time of muscle contraction are highly concentrated in the blood so that calcium that should be filtered in the kidneys precipitates and forms stones in the urinary tract. This aim of the research is to find out the description and percentage of the results of urine sediment examination of calcium oxalate crystals in convection workers in Kalipucang Village, Batang District. This type of research is descriptive. The samples in this study were 22 morning urine samples obtained from convection workers in Kalipucang Village, Batang District, taken using purposive sampling technique. Examination of urine sediment was carried out by microscopic method. Of the 22 samples of convection workers, 1 sample (4.55%) ++ calcium oxalate crystals, 13 samples (59.09%) +++ calcium oxalate crystals and 8 samples (36.36%) were negative for calcium oxalate crystals. The results of the study on the description of urine sediment calcium oxalate crystals in convection workers in Kalipucang Village, Batang District concluded that out of 22 samples there were 1 sample (4.55%) ++ calcium oxalate crystals, 13 samples (59.09%) +++ calcium oxalate crystals and 8 samples (36.36%) tested negative for calcium oxalate crystals in the urine.